Legal-lay discourse and procedural justice in family and county courts - Grieshofer, Tatiana (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2024)
Focusing on adversarial legal settings, this Element explores discursive practices in court proceedings which often involve unrepresented parties - private family proceedings and small claims cases. Such proceedings present the main caseload of county and family courts, but pose immense challenges when it comes to legal-lay communication. Drawing on court observations, alongside textual and interview data, the Element pursues three aims: (1) developing the methodological and theoretical framework for exploring discursive practices in legal settings; (2) establishing the link between legal-lay discourse and procedural justice; (3) presenting and contextualising linguistic phenomena as an inherent part of court research and practice. The Element illustrates how linguistic input can contribute to procedural changes and court reforms across different adversarial and non-adversarial legal settings. The exploration of discursive practices embedded in court processes and procedures consolidates and advances the existing court research conducted within the fields of socio-legal studies and forensic linguistics. This title is also available as Open Access on Cambridge Core.
Legal-lay discourse -- Discourse of civil and family proceedings -- Discursive practices, procedural justice, and legal participation -- Language data and empirical methods -- Discursive practices in child arrangements proceedings -- Discursive practices in financial remedy proceedings -- Discursive practices in county courts -- Concluding thoughts and future directions.
Title from publisher's bibliographic system (viewed on 28 Mar 2024).
Keywords: Procedure (Law); Courts; Court proceedings; Domestic relations courts; County courts; Law -- Language; Due process of law